Increasing the Knowledge of Women Farmer Through Household Counseling on Food Safety in Sumberejo Village, Magelang Regency - Maria Marina Herawati; Yoga Aji Handoko; Alfred Jansen Sutrisno; Maria Maria; Liska Simamora; Yuliawati Yuliawati; Bayu Nuswantara; Bistok Hasiholan Simanjuntak (Pascasarjana Universitas Mataram, 2024)
Food safety is the condition and effort needed to prevent food from three possible contaminations, namely: biological, chemical and other contamination that can disturb, harm and endanger human health. Sumberejo Village is a Partner of Faculty of Agriculture and Business, Universitas Kristen Satya Wacana. Sumberejo Village has potential resources in the form of vegetables. It is supported by climate and temperature conditions that are suitable for vegetable production. One of the superior commodities produced in Sumberejo Village is beetroot fruit. Processing agricultural products into processed food products is an effort to increase economic value when prices fall or during harvest time. Processing beet tubers into processed products such as cookies, beetroot tea bags, cakes are one way to reduce losses due to falling prices and increase the selling value of beet tubers. Knowledge and safe food processing practices are very necessary in food processing activities. Through food safety education activities, it is hoped that the women farming community in Sumberejo village will be able to process beet tubers in accordance with the concept of food safety. The aim of this Community Service activity is to provide knowledge and understanding of female farmers in Sumberejo Village regarding food safety and efforts to prevent contamination during food processing and producing food that is safe for consumption by the community. Based on the results of implementing safety education activities in Sumberejo Village, it can be concluded that there has been an increase in knowledge about food safety. It can be seen in the results of the questionnaire that knowledge about food safety is important because it concerns health